Cloudy in the Educational Process of Higher Education Institutions Need to Use Technologies - Associate Professor Aripov M.M; Said Akbar Gafurov (Peerian Journals Publishing, 2023)
In this state, the use and application of cloud technology in the educational process, the problems of its use, and the significance of the use of cloud technology in the educational process are analyzed in Uzbekistan. Izucheno, chto ispolzovanie oblachnyx tekhnologiy v obrazovatelnom protsese pozvolyaet ispolzovat bolee shirokiy spectr form i metodov, yavlyaetsya odnim iz sovremennyx sposobov prostit i oblegchit process obuchenia.
Keywords: training; interactive method; cloud technology; information